Effects of Different Light Environments with Varying Spectral Composition on the Axial Lengths and Scleral Specificity Protein 1 and Collagen Type I Expression in Juvenile Guinea Pigs - Yuan, Jianbao; Wang, Yuliang; Xu, Xinyu; Yang, Mei; Fan, Yipeng; Shi, Xiaopan; Sun, Lulu; Shan, Mingyu; Ma, Lei (Folia biologica, 2024)
The study aimed to investigate changes in the eye axial length in juvenile guinea pigs and the expression of scleral specificity protein 1 (Sp1) and collagen type I (Col-I) under different light environments with varying spectral composition. The animals were randomly divided into five groups: natural light (N), LED light with a low colour temperature (L), E light (E), Fulia light (F), and Gulia light (G). Axial lengths were measured every two weeks, and the expression of Sp1 and Col-I in the sclera was assessed by immunohistochemistry, Western blot and RT-qPCR. After 4, 6, 8, 10, and 12 weeks of light exposure, the L and G groups showed considerably longer axial lengths than the N group, with the L group exhibiting significantly longer axial lengths compared with the E and F groups. The protein and mRNA expression levels of Sp1 and Col-I, ranked from highest to lowest, were as follows: N, E, F, G, and L. The expression of Sp1 and Col-I was positively correlated, but both were negatively correlated with the length of the eye axis. The E group demonstrated higher Sp1 and Col-I expression than the other artificial light groups. Artificial light with a continuous, full spectrum lacking peaks and valleys can inhibit the elongation of the eye axis in juvenile guinea pigs and has a protective effect against myopia. There may be a certain relationship between Sp1 and Col-I, and the transforming growth factor-β1-Sp1-Col-I signalling pathway may play a crucial role in myopic scleral extracellular matrix remodelling.
Keywords: axiální délka oka; Collagen Type I; myopie; Gene Expression Regulation; světlo; messenger RNA; RNA, Messenger; kolagen typu I; Light; Sclera; mužské pohlaví; zvířata; Sp1 Transcription Factor; skléra; Animals; Myopia; Male; transkripční faktor Sp1; regulace genové exprese; morčata; Axial Length, Eye; Guinea Pigs